1999
DOI: 10.1287/mksc.18.4.527
|View full text |Cite
|
Sign up to set email alerts
|

The Variety of an Assortment

Abstract: Consumers rank variety of assortment right behind location and price when naming reasons why they patronize their favorite stores. Consumers care about variety because they are more likely to find what they want when going to a store that offers more varied assortments. When tastes are not well formed or are dynamic, perceived variety matters even more because of the desire to become educated about what is available while maintaining flexibility. Variety perception also matters when the variety-seeking motive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
272
1
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(299 citation statements)
references
References 19 publications
14
272
1
12
Order By: Relevance
“…Thus, recent research has shown that increasing the size of the choice set may lower the overall probability of purchase (Chernev 2003a;Dhar 1997;Huffman and Kahn 1998;Iyengar and Lepper 2000). Most of this research, however, has examined the impact of assortment on choice without explicitly focusing on the potential relationship between features describing choice alternatives (although see Hoch, Bradlow, and Wansink 1999;Kahn and Wansink 2004). As a result, it has been implicitly assumed that all product features influence consumer decision processes and choice in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, recent research has shown that increasing the size of the choice set may lower the overall probability of purchase (Chernev 2003a;Dhar 1997;Huffman and Kahn 1998;Iyengar and Lepper 2000). Most of this research, however, has examined the impact of assortment on choice without explicitly focusing on the potential relationship between features describing choice alternatives (although see Hoch, Bradlow, and Wansink 1999;Kahn and Wansink 2004). As a result, it has been implicitly assumed that all product features influence consumer decision processes and choice in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…For instance Broniarczyk, Hoyer, and McAlister (1998) found that a smaller sized product offering could actually be perceived by consumers to offer greater assortment than a larger sized product offering when it included consumers' favorites or occupied a larger total shelf space. Hoch, Bradlow, and Wansink (1999) found that, holding product-offering size constant, assortment perceptions could be increased if products were dissimilar and offered unique features. Van Herpen and Pieters (2002) found that although product-offering size exerted a significant influence on assortment perceptions, attribute dispersion and disassociation exerted an even greater influence.…”
Section: Effects Of Assortment Size and Entropy On Quality And Difficmentioning
confidence: 99%
“…Mesmo assim, Hoch et al (1999) confirmam que os varejistas reconhecem que os consumidores valorizam a variedade de sortimento da loja e consideram essa variável importante na tomada de decisão de compra.…”
Section: Análise Dos Resultados Análise Do Componente Sortimentounclassified
“…O sortimento e a variedade são fatores relevantes de competitividade e diferenciação. Hoch, Bradlow e Wansink (1999) confirmam que os varejistas reconhecem que os consumidores valorizam o sortimento como uma variável importante na tomada de decisão de compra. Levy e Weitz (2012) apresentam a componente sortimento como "o número de itens diferentes em uma categoria de mercadoria, sendo que cada item é denominado como unidade de manutenção de estoque (stock keeping unit -SKU), e variedade como o número de categorias diferentes oferecidas por um varejista" (p. 314).…”
Section: Sortimento No Varejounclassified